A Chemical study of the thistle plant Tribulus terrestris L., widespread in the Hama countryside in Syria - ضايع رشا; يوسف عزيزة; صقر لينا (Latakia University Journal -Medical Sciences Series, 2024)
The aim of the current study is a chemical study on Tribulus terrestris: phytochemical screening was conducted on its’ various parts (leaves, flowers, fruits) to evaluate a few secondary metabolites, total phenol and flavonoid content assays. Extracts were prepared using established methods. Phenol content was quantified using Gallic acid (G.A) (500 Mcg/ml) using Folin-ciocaltu method, and flavonoid assay using Rutin (0.0161 mg/ml) using Aluminium trichloride method via spectrophotmeter. The screening revealed differences in the composition according to the used part, tannins, phenols, cardiac glycosides, and coumarin found in all parts, alkaloids detected in leaves, flavonoids and saponins in flowers and leaves, terpenoids were absent in all parts. Phenol content reached in flowers: 16.0034 mg equivalent to G.A/1g dry powder, leaves: 22.3434 mg/1g, fruits: 10.151 mg/1g. Whereas, flavonoid content reached in flowers: 0.024 mg equivalent to Rutin/1g dry powder, leaves: 0.0444 mg/1g, fruits: 0.00953 mg/1g.